Pengaruh Karakter Figur, Komunikasi Politik Digital Terhadap Keputusan Gen Z Pada Pilkada 2024 Dengan Di Moderasi Literasi Politik (Studi Kasus Kota Bukittinggi Sumatera Barat) - Beny Yusrial; Heru Aulia Azman (CV. ITTC INDONESIA, 2026)
This study examines the influence of candidate characteristics and digital political communication on Generation Z’s voting decisions in the 2024 Bukittinggi local election, with digital political literacy as a moderating variable. Using a quantitative survey of 379 respondents and analyzed through SEM-PLS, the findings indicate that candidate characteristics and digital political communication positively and significantly affect voting decisions, with digital political communication emerging as the most dominant factor. Digital political literacy significantly influences voting decisions in a negative direction, suggesting that higher literacy levels make Generation Z more critical in political choices. Furthermore, digital political literacy weakens the effect of candidate characteristics and strengthens the effect of digital political communication on voting decisions. These findings highlight the role of digital competence in shaping youth political behavior in the digital democracy era.